2023
DOI: 10.3389/fpsyg.2023.1151399
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between sleep disturbance and obsessive– compulsive symptoms: the mediation of repetitive negative thinking and the moderation of experiential avoidance

Abstract: BackgroundStudies have found that sleep disturbance is associated with obsessive–compulsive symptoms. This study aimed to elaborate on the mediating and moderating mechanisms between these two variables. We hypothesized that repetitive negative thinking plays a mediating role in the relationship between sleep disturbance and obsessive–compulsive symptoms, and experiential avoidance plays a moderating role.MethodThis study included 639 Chinese adults. A questionnaire survey was used to assess sleep quality, obs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 49 publications
(71 reference statements)
0
1
0
1
Order By: Relevance
“…No que tange aos consequentes ou às comorbidades relacionadas ao PRN, sabe-se que esse construto funciona como um mecanismo que pode levar a sintomas de depressão e ansiedade (Everaert & Joormann, 2019), transtornos alimentares (Sala et al, 2019) e declínio cognitivo em idosos (Marchant et al, 2020;Schlosser et al, 2020). Além disso, estudos demonstram o papel mediador do PRN em diferentes variáveis, como no impacto do distúrbio do sono nos sintomas do transtorno obsessivo-compulsivo (Zhao et al, 2023); na relação entre evitação e sofrimento emocional em universitários (Munsamy et al, 2023); na manutenção de sintomas de ansiedade generalizada e da percepção da satisfação com a vida, comprometendo o bem-estar (Peixoto et al, 2023); na relação entre o perfeccionismo desadaptativo e o esgotamento acadêmico ou na ansiedade cognitiva de provas em estudantes universitários (Garratt-Reed et al, 2018;Jolly et al, 2022).…”
Section: Correlatos Do Pensamento Repetitivo Negativounclassified
“…No que tange aos consequentes ou às comorbidades relacionadas ao PRN, sabe-se que esse construto funciona como um mecanismo que pode levar a sintomas de depressão e ansiedade (Everaert & Joormann, 2019), transtornos alimentares (Sala et al, 2019) e declínio cognitivo em idosos (Marchant et al, 2020;Schlosser et al, 2020). Além disso, estudos demonstram o papel mediador do PRN em diferentes variáveis, como no impacto do distúrbio do sono nos sintomas do transtorno obsessivo-compulsivo (Zhao et al, 2023); na relação entre evitação e sofrimento emocional em universitários (Munsamy et al, 2023); na manutenção de sintomas de ansiedade generalizada e da percepção da satisfação com a vida, comprometendo o bem-estar (Peixoto et al, 2023); na relação entre o perfeccionismo desadaptativo e o esgotamento acadêmico ou na ansiedade cognitiva de provas em estudantes universitários (Garratt-Reed et al, 2018;Jolly et al, 2022).…”
Section: Correlatos Do Pensamento Repetitivo Negativounclassified
“…Although, hormonal dysregulation and delayed sleep phase disorder (DSPD) in patients with OCD point to the possible role of abnormal circadian rhythms [ 9 ]. Moreover, it has been reported that more severe OCD symptoms are associated with more significant sleep disturbance [ 10 ]. Melatonin, a serotonin product, is released from the pineal gland and plays a key role in regulating the circadian rhythm.…”
Section: Introductionmentioning
confidence: 99%